Mediating effect of health consciousness in the relationship of lifestyle and suboptimal health status: a cross-sectional study involving Chinese urban residents. Issue 10 (26th October 2020) - Xue, Yunlian; Liu, Guihao; Feng, Yefang; Xu, Mengyao; Jiang, Lijie; Lin, Yuanqi; Xu, Jun
Abstract : Objective: Suboptimal health status (SHS), a third state between good health and disease, can easily develop into chronic diseases, and can be influenced by lifestyle and health consciousness. No study has surveyed the intermediation of health consciousness on the relationship between lifestyle and SHS. This study aimed to analyse the association of lifestyle and SHS, and intermediation of health consciousness in Chinese urban residents. Design: A cross-sectional face-to-face survey using a four-stage stratified sampling method. Participants: We investigated 5803 Chinese urban residents aged 18 years and over. We measured SHS using the Sub-Health Measurement Scale V1.0. We adopted a structural equation model to analyse relationships among lifestyle, health consciousness and SHS. We applied a bootstrapping method to estimate the mediation effect of health consciousness. Results: Lifestyle had stronger indirect associations with physical ( β −0.185, 95% CI −0.228 to −0.149), mental ( β −0.224, 95% CI −0.265 to −0.186) and social SHS ( β −0.216, 95% CI −0.257 to −0.179) via health consciousness than direct associations of physical ( β −0.144, 95% CI −0.209 to −0.081), mental ( β −0.146, 95% CI −0.201 to −0.094) and social SHS ( β −0.130, 95% CI −0.181 to −0.077). Health consciousness has a strong direct association with physical ( β 0.360, 95% CI 0.295 to 0.427), mental ( β 0.452, 95% CI 0.392 to 0.510) and social SHS ( β 0.434, 95% CI 0.376 to 0.490). Ratio of mediating effect of health consciousness to direct effect of lifestyle with physical, mental and social SHS was 1.28, 1.53 and 1.66, respectively. Conclusions: Health consciousness was more important in preventing physical, mental and social SHS than lifestyle. Therefore, it might be useful in changing unhealthy lifestyle and reducing the influence of poor lifestyle on physical, mental and social SHS.